Isolation, identification and characterization of chitinase producing Trichoderma flavofuscum - D.B. GAWADE, K.K. SURYAWANSHI, R.U. THOSAR* and (Indian Phytopathology, 2016)
Chitinase hydrolyzes chitin, a biopolymer of N-acetylglucosamine which is being widely used in biological and agricultural research. Optimization of chitinase production by Trichoderma flavofuscum was conducted in this experiment. Trichoderma was isolated from soil sample and identified on basis of morphological character studied under microscope and confirmation was done. The identified pure culture of T. flavofuscum was inoculated on Chitin rich CZ Broth and incubated for 10 days and filtrate was studied for extracellular chitinase activity by DNS method. During this experiment, it was observed that peak chitinase activity was observed at 90 minute after reaction time.